Cortés, A. Y Manjarrez, J. (eds.) (2018). Género, migraciones y derechos humanos. Barcelona: Edicions Bellaterra, S. L. - Benincasa, Valentina (PARTECIPAZIONE E CONFLITTO, 2019)
For Book Reviews Abstract is not Required